2021
DOI: 10.1128/mbio.03482-20
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Antibiotic Tolerance Shapes Resistance Development in Chronic Pseudomonas aeruginosa Infections

Abstract: The widespread use of antibiotics promotes the evolution and dissemination of resistance and tolerance mechanisms. To assess the relevance of tolerance and its implications for resistance development, we used in vitro evolution and analyzed the inpatient microevolution of Pseudomonas aeruginosa, an important human pathogen causing acute and chronic infections. We show that the development of tolerance precedes and promotes the acquisition of resistance in vitro, and we present evidence that similar processes s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 64 publications
5
76
0
Order By: Relevance
“…Indeed, consistent with previous in vitro evolution studies in E. coli ( 18 ) and Pseudomonas aeruginosa ( 61 ) which reported that tolerance precedes resistance, we also observed that a tolerant mutant (TOL2) appeared in an earlier cycle than a resistant mutant (RES2) in lineage 2 ( Fig. 1b and c ).…”
Section: Observationsupporting
confidence: 91%
“…Indeed, consistent with previous in vitro evolution studies in E. coli ( 18 ) and Pseudomonas aeruginosa ( 61 ) which reported that tolerance precedes resistance, we also observed that a tolerant mutant (TOL2) appeared in an earlier cycle than a resistant mutant (RES2) in lineage 2 ( Fig. 1b and c ).…”
Section: Observationsupporting
confidence: 91%
“…Different conditions, compounds and modes of growth that may take place during the infection process might transiently increase the resistance of this opportunistic pathogen to several antimicrobial treatments, thus hindering the eradication of the infecting bacterial population. Further, recent work has shown that the early appearance of tolerance mutations facilitates the evolution of AR [ 110 ], a feature of particular relevance in the case of chronic P. aeruginosa infections [ 111 ].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…Genes associated with QS, iron acquisition, phenazine biosynthesis, and multidrug efflux were shown to have mutated to promote survival and progression to chronic infection [62]. Chronic colonisation is associated with genotypic and phenotypic changes, such as reduced QS [63], metabolism [64], and motility [65] and overproduction of alginate [66] and increased antibiotic resistance [67,68]. During the chronic colonisation stage, P. aeruginosa changes from a non-mucoid motile phenotype to a mucoid biofilm former that is capable of evading host responses and antibiotics, at which point it becomes very difficult to eradicate.…”
Section: P Aeruginosa Infection In Cfmentioning
confidence: 99%